Neogene-Quaternary onshore record in the lower Ebro river incised palaeovalley (Ebro margin, Catalan Coastal Range, NE Iberia). - Arasa-Tuliesa, A.; Cabrera, Lluís (Geologica Acta, 2018)
The lower Ebro is a bedrock-alluvial mixed incised valley with a persistent degradational stacking architecture developed from latest Serravallian(?) to Holocene. This degradational pattern was probably controlled by isostatic rebound in NE Iberia and punctuated by major relative sea level changes that temporally accentuated or attenuated the palaeovalley entrenchment and sediment retention. Six allostratigraphic units in the palaeovalley constitute the onshore record of its evolution and the opening and connection of the Ebro Basin with the Mediterranean. This paper deals with the analysis and reinterpretation of these units in order to precise the sequence of events that took place on the onshore part of the Catalan continental margin during the Ebro River drainage entrenchment. Plausible chronology and palaeogeographic evolution of the Neogene-Quaternary drainage incision in the lower Ebro are also proposed. The early evolutionary stages of the incised palaeovalley (Latest Serravallian?-Tortonian-Early Messinian, from 11.63–9? to near 5.6Ma) were dominated by entrenchment and intense sediment transfer from the onshore to the offshore zones (erosion surface S2). These processes were only punctuated by the sedimentation of the alluvial palaeovalley unit M2 (late Messinian). The polygenetic onshore erosion surfaces S2 and S3 are linked here with the onshore erosive processes that fed the sedimentation of the terrigenous shelf-slope system of the offshore Castellón group and considered coeval with the offshore Messinian erosion surfaces (reflectors M and m). During a further evolutionary stage (Pliocene to Early Pleistocene from 5.3 to approximately 2Ma) the Early Pliocene major Mediterranean reflooding caused some sediment retention in the incised palaeovalley (sedimentation of unit P) but sediment transfer into the offshore remained very effective. In the last evolutionary stage (Early Pleistocene-Holocene, from 2Ma to present) the palaeovalley became again mainly degradational (generation of erosion surfaces S4 to S6 and sedimentation of stepped alluvial terraces Q1-2 to Q4). The onshore stratigraphic record, including the allostratigraphic units P and Q1-2 to Q4 and the related bounding surfaces S3 to S6, is correlated with the sedimentation of the terrigenous shelf-slope system of the offshore Ebro group.